HUBUNGAN ANTARA KESABARAN DENGAN STRES AKADEMIK PADA MAHASISWA DI PEKANBARU - Indah Indria; Juliarni Siregar; Yulia Herawaty (UIR Press, 2019)
Abstract This study aims to determine the relationship between patience and academic stress in the college student environment in Pekanbaru. This study involved 120 samples of college students of University X which selected by using cluster sampling technique. Data was collected by used patience scale that compiled by Rozi and El Hafizh, and academic stress scale compiled by Wicaksana (2017). Based on the results of Pearson Product Moment correlation analysis, the correlation coefficient (r) = -0,559 and significance value 0,000 (p <0.05). This data shows that there is a significant negative correlation between patience and academic stress in college students at the University X. The higher of patience is followed by the lower of academic stress on the college students and vice versa, lower of patience will be followed by the higher of academic stress experienced by college students. Keywords : patience, academic stress, religious coping Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara kesabaran dengan stres akademik pada mahasiswa Universitas X di Pekanbaru. Penelitian ini melibatkan 120 sampel mahasiswa Universitas X yang dipilih menggunakan teknik cluster sampling. Alat pengumpulan data berupa skala sabar yang disusun oleh Rozi dan El Hafiz dan skala stres akademik yang disusun oleh Wicaksana (2017). Berdasarkan dari hasil analisis uji korelasi Pearson Product Moment, maka diperoleh nilai koefisien korelasi (r) = -0,559 dengan nilai signifikansi 0,000 (ρ <0,05). Hal ini menunjukkan bahwa terdapat korelasi negatif yang signifikan antara sabar dengan stres akademik pada mahasiswa Universitas X di Pekanbaru. Semakin tinggi kesabaran mahasiswa maka akan semakin rendah stres akademik mahasiswa dan begitu juga sebaliknya, semakin rendah kesabaran maka akan semakin tinggi pula stres akademik mahasiswa. Kata kunci : sabar, stres akademik, koping religius